Concept of Parenting in the Digital Era - Zubaidah, Zubaidah; Rahmayanty, Dinny; Finanjani, Syakila; Setiawati, Yodia; Aryanto, Randy (Faculty of Education Universitas Negeri Malang, 2024)
The digital era has introduced new challenges for parents in educating their children, as information technology and social media have a significant influence on children's daily lives. Furthermore, the development of digital technology has had a significant impact on parenting and child-rearing practices. The purpose of this article is to help parents, prospective parents, and educators understand the concept of parenting, with a specific focus on the principles of positive parenting, to address the challenges of parenting in the digital age and ensure that children are shielded from the negative effects of technology. The method used in this study involves a literature review that discusses similar topics under the title. The findings reveal positive principles in parenting that help parents understand appropriate parenting methods for children born in the digital era, thus minimizing the negative impact of technology on children.